Beautiful particularity: using phronetic, iterative, and heuristic approaches to a positively deviant case. Issue 4 (2nd October 2019) - Huffman, Timothy P.; Tracy, Sarah J.; Bisel, Ryan S.
ABSTRACT: Some events are so important and transformative that it is valuable to understand what led to the event so others may potentially reproduce it. But making claims from single cases has to be done carefully. This paper explains how to draw useful claims out of unique and inspiring cases. It reviews the methodological strategies that drove a case study looking at how hope and compassion changed the outcome of a would-be school shooting. Specifically, this paper demonstrates the value and process of choosing a positively deviant event on which to focus a case study. Further, it outlines how to approach qualitative analysis from a phronetic, iterative, and heuristic stance. Finally, it offers recommendations for how to make claims made from a single case and how to position them in the context of other studies.